Kick-starting the experience – an experience-based typology of spectators at a live action sport event. Issue 5 (20th October 2019) - Kruger, Martinette; Saayman, Melville
ABSTRACT: This exploratory research set out to identify the management factors involved in creating a memorable experience at a live action sport event and, based on these factors, identify different spectator segments. The research also set out to determine whether these segments differ in terms of socio-demographic and behavioural characteristics and in motives for attending. This research makes an important contribution to a greater understanding of action sports spectators, specifically spectators at live events with daring and thrilling stunts, and contributes to the literature on managing and marketing of entertaining sports events of this nature to the specific market segments who are attracted to these events. The research proposes an EEC-experience-based typology ( Event aficionados, Entertainment seekers and Crowd pleasers ) of live action sport spectators that could be applied to other live action sport events. This research concluded that there are different types of sport spectators and that their needs differ.